Coping with cystic fibrosis: An analysis from the sibling's point of view. (25th June 2021) - Milo, Francesco; Ranocchiari, Silvia; Lucidi, Vincenzina; Tabarini, Paola
Abstract: Background: Cystic fibrosis (CF) is a chronic, life‐threatening condition that results in life‐long morbidity and premature mortality. CF has a significant impact on healthy siblings' adaptation and well‐being. Siblings of patients with a chronic disease may experience psychological difficulties, such as anxiety, depression symptoms and troubles in adaptation. This study aimed to explore the participants' experiences of growing up with a CF patient diagnosed at a paediatric age and their adaptation strategies. Methods: We enrolled eight CF siblings (adolescents and young adults) in a 6‐month focus group sessions programme. Each session had two phases (psychoeducational and experiential). Transcripts were analysed and grouped through grounded theory analysis to elaborate on data‐driven theory. Results: We identified 14 subthemes by which the raw data could be organized. All the subthemes were gathered together according to the axial coding process into six themes (illness, changes, communication, avoidance, normalization, and protection and care). We then grouped the six themes into two main themes ('Growing up with a CF brother or sister' and 'Finding the right distance') and conceptualized the grounded theory 'Keeping the right distance'. The participants described the evolving process of maintaining a balance between the illness of their brother or sister, family organization and their own needs. Conclusions: Knowing siblings' experiences and their common strategies to deal with the experience of having a brother or sister with a chronic health condition may be useful to ensure more tailored and specific interventions.